Uptake of genetic counseling and testing in a clinic‐based population of women with breast cancer. (23rd March 2022) - Wehbe, Alexandra; Manning, Mark; Assad, Hadeel; Purrington, Kristen S.; Simon, Michael S.
Abstract: Background: The study was conducted to evaluate racial differences in referral and uptake of genetic counseling (GC) in a clinic‐based population of women with breast cancer. Methods: Medical records of 150 breast cancer patients at the Karmanos Cancer Institute were reviewed to determine eligibility for GC according to National Comprehensive Cancer Network guidelines, GC referral rates, and appointment completion rates. Logistic regression was used to assess the relationship between demographic and clinical factors and GC eligibility and referral. Results: The mean age at diagnosis was 57.1 (SD 12.6) and 66% of the women were Black. There were 91 women (60.7%) eligible for GC and of those, 54 (61.4%) were referred. After multivariable analyses, factors associated with reduced eligibility were older age at diagnosis (OR = 0.91, 95% CI [0.87, 0.95]) and Black race (OR = 0.37, 95% CI [0.15, 0.96]). After additional multivariable analysis, eligibility was associated with an increased likelihood of referral (OR = 5.97, 95% CI [2.29, 15.56]), however, Medicare versus private insurance was associated with a lower likelihood for referral (OR = 0.32, 95% CI [0.12–0.80]. Of those referred, 49 (76.6%) completed an appointment, and 47 had genetic testing. Women with Medicare were also less likely to complete an appointment. Race had no impact on referral or appointment completion. Conclusions: There were no racial differences in GC referral or appointment completion in a clinic‐based sample of women with breast cancer. Further interventions are needed to promote increased referral and appointment completion for women with breast cancer who are eligible for GC. Abstract : There were no racial differences in GC referral or appointment completion in a clinic‐based sample of women with breast cancer. Further interventions are needed to promote increased referral and appointment completion for women with breast cancer who are eligible for GC.